2010
DOI: 10.1186/1471-2296-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the quality of antibiotic prescribing in Primary Care: Qualitative evaluation of a blended learning intervention

Abstract: BackgroundThe Stemming the Tide of Antibiotic Resistance (STAR) Educational Program aims to enhance the quality of antibiotic prescribing and raise awareness about antibiotic resistance among general medical practitioners. It consists of a seven part, theory-based blended learning program that includes online reflection on clinicians' own practice, presentation of research evidence and guidelines, a practice-based seminar focusing on participants' own antibiotic prescribing and resistance rates in urine sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Intervention content was based on theories of behaviour change and particularly focused on increasing self-efficacy, one's belief that one can carry out a particular behaviour at a given time. 16,17 Clinicians reported being more confident in diagnosing an infection when using the CRP test and in explaining a nonprescribing decision to patients, and this appeared to be a result of training videos provided within interventions. Clinicians' expectations of the outcome of a consultation are also likely to have changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention content was based on theories of behaviour change and particularly focused on increasing self-efficacy, one's belief that one can carry out a particular behaviour at a given time. 16,17 Clinicians reported being more confident in diagnosing an infection when using the CRP test and in explaining a nonprescribing decision to patients, and this appeared to be a result of training videos provided within interventions. Clinicians' expectations of the outcome of a consultation are also likely to have changed.…”
Section: Discussionmentioning
confidence: 99%
“…The STAR study evaluated a multifaceted educational intervention delivered through both online and outreach visit training, and was centred on communication skills. [16][17][18][19][20][21][22][23][24][25][26] Clinicians reported that communication skills training gave them an additional insight into their patients' agendas, which they felt would reduce future unnecessary consultations, but required an initial investment of longer consultations. The current study found that only a minority of clinicians specifically mentioned the advantage of the communication skills and most concentrated on the benefits of the patient booklet.…”
Section: Discussionmentioning
confidence: 99%
“…It is understandable that the student verbalizes comfort and safety in relation to scientific papers indicated by the professor regarding the content to be learned, because although there is a strong supply of online publications, in general, students still do not have security for interpret their findings. (18) Another analytical facility is the very ease of obtaining the article by the student, a lazy attitude. In this sense, the role of the teacher-tutor in Moodle deserves reflection, in that one can only monitor whether or not the student opened the text (which is possible via control tools) or provoke them with activities that may denote a real reading and reflection.…”
Section: Discussionmentioning
confidence: 99%
“…As a possible solution to overcome this uncertainty they gave some recommendations such as better access to rapid diagnostic tests and the use of clinical guidelines. It has been shown that access to rapid diagnostic tests improve the use of antibiotics, as well as the respect of clinical guidelines which affects the rationalization of the use of antibiotics (19)(20)(21)(22). Some study participants cited the option of deferred prescribing of antibiotics as a possible solution in equivocal cases and scheduling follow-up examination after a short time period (3-4 days).…”
Section: Discussionmentioning
confidence: 99%